Deregulated E2F5/p38/SMAD3 Circuitry Reinforces the Pro‐Tumorigenic Switch of TGFβ Signaling in Prostate Cancer. Issue 11 (14th March 2016) - Majumder, Subhadipa; Bhowal, Ankur; Basu, Sanmitra; Mukherjee, Pritha; Chatterji, Urmi; Sengupta, Sanghamitra
Abstract : Transforming growth factor‐β signaling exerts divergent effects on normal and cancer cells, although mechanism underlying this differential behavior remains unclear. In this study, expression of 94 genes pertaining to the TGF‐β signaling pathway was compared between tumor and benign tissue samples from the human prostate gland to identify major discriminators driving prostate carcinogenesis. E2F5 was identified as one of the most deregulated genes in prostate cancer tissues, predominantly in samples with Gleason‐score 6. Expression of other deregulated components of TGF‐β signaling was examined by qRT‐PCR, Western blot, and immune‐staining. Function of E2F5 and p38 in prostate cancer was investigated using siRNA‐treatment of PC3 cell‐line followed by analyses of associated components and cell cycle. Observations revealed that E2F5 overexpression was accompanied by significantly higher phosphorylation of SMAD3 at Ser‐208 in the linker region (pSMAD3L) and p38 in tumor tissue. A striking difference in SMAD3 phosphorylation, marked by preponderance of pSMAD3L and pSMAD3C (Ser‐423 and 425) in tumor and benign tissues, respectively was noted. Co‐localization of E2F5 with pSMAD3L in the nuclei of tumor and PC3 cells indicated a functional interface between the proteins. Downregulation of E2F5 and p38 in PC3 cells resulted in marked reduction of phosphorylation of SMAD3 and perturbation of cell cycle with an arrest of cells in G1 . Our findings unearthed that E2F5/p38 axis played a cardinal role in uncontrolled cellular proliferation in prostate cancer through pSMAD3L activation. It also underscores a strong potential for E2F5 to be incorporated as a tool in early detection of prostate cancer. J. Cell. Physiol. 231: 2482–2492, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Transforming growth factor‐β signaling exerts divergent effects on normal and cancer cells. Our study demonstrates that dysregulated E2F5/p38/pSMAD3L axis plays an important role in converting tumor‐suppressive TGFβ signaling into pro‐tumorigenic signaling.